Country Branding: Qualitatively New Shifts in Country Image Communication - Dagytė, Ina; Zykas, Aurelijus (Sociologija. Mintis ir veiksmas, 2015)
In spite of the fact that the rational country image communication is severely criticised by some scholars, it is gaining a big importance worldwide. It is applied for strengthening identities and developing economy, politics, and culture of the countries. In this paper, the phenomena of country branding, emerged at the end of the 20th century in Europe, is discussed in the new perspective, comparing it to other approaches of the country image communication, i.e. the traditions of the USSR and of the USA, trying to find its distinctive features.